Teaching mathematics to all children : designing and adapting instruction to meet the needs of diverse learners - Tucker, Benny F.; Singleton, Ann H.; Weaver, Terry L. (Upper Saddle River, NJ : Prentice Hall, 2002)
With the composition of today's classroom in mind, this book approaches teaching and planning elementary mathematics by using methods that accommodate the diverse learning needs of any student having difficulties with basic mathematics.
Includes bibliographical reference and index.
Keywords: Mathematics -- Study and teaching (Elementary).